Amine metabolites in ventricular cerebrospinal fluid in coma. - Yates, C M (1979)
The concentrations of homovanillic acid (HVA), 3-methoxy, 4-hydroxyphenylglycol (MHPG), and 5-hydroxyindolylacetic acid (5-HIAA) were measured in samples of ventricular cerebrospinal fluid (CSF) taken from 15 patients who were comatose as a result of an acute head injury, a tumour, or a cerebrovascular accident. The metabolite levels were not related to the ventricular fluid pressure. In the eight patients who recovered and from whom serial samples of CSF were obtained, the metabolite levels did not change, except for two patients in whom HVA increased as coma progressed. The concentration of MHPG, but not of HVA or 5-HIAA, was greater (P less than 0.02) in the five patients who died without regaining consciousness than in the 10 patients who recovered.